Somewhere in between towns, markets, and neighbors: Agricultural transition in the rural-urban interface of Bangalore, India - Linda Steinhübel (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
This paper presents a flexible conceptual and methodological framework to model the dynamics of agricultural transition in the increasingly complex rural-urban interfaces of large cities. Our empirical analysis is based on data of a household survey conducted in the rural-urban interface of Bangalore, India. In our analysis we follow a polycentric perspective of urbanization and introduce a two-dimensional variable to measure its effects. Furthermore, we accommodate high input and crop diversity by applying a Structured Additive Regression (STAR) model. Our results show that satellite towns and road infrastructure are the main channels by which urbanization drives agricultural transition. Access to satellite towns appears to be more strongly associated with the modernization of smallholders' management systems than access to the urban center of Bangalore. Our results suggest that more flexible models are necessary to understand the dynamics of agricultural transition in the surroundings of fastgrowing large towns, the kind of town expected to be dominating the urbanization trend in the coming decades.
Keywords: Q12; R11; C14; 330; Agricultural change; Urbanization; Structured Additive Regression; Geosplines; India